Différenciations territoriales et insertion dans la mondialisation : le cas de l’énergie en Inde - Nicolas Mazzucchi (EchoGéo)
The energy situation of India is impacted by the intense economic development of the country for fifteen years. The goal of energy independence, center of India’s energy policy, is continuously challenged with the growth of oil and electricity demand. As a consequence India is forced to enter the global competition by developing the national oil companies’ international deployment as well as in using foreign – mostly Western and Chinese – energy technologies (nuclear, renewables, etc.). At the same time, globalization is creating a growing difference among Indian states as the most developed are thoroughly integrated and the poorest seem isolated from the global market and energy networks.